THE COMMUNISM IN SERBIA IN THE AFTERMATH OF ITS FORMAL DOWNFALL (1990-2000) - todorovic, vladica s (Political Review, 2024)
With this paper, the author’s objective was to prove that communism existed in Serbian society even after its downfall from 1990 to 2000. The ruling Socialist Party of Serbia (SPS), derived from the Communist Party, aimed to preserve such a system even in new circumstances. Thus, as time went by when presumably the danger had passed, they founded the JUL in 1994. They openly advocated the previous value system, which existed during the one-party system, with no intention of turning Serbia into a democratic country and reforming different parts of society. If the changes in 2000 had not occurred, the SPS and related parties would still have kept Serbia in a kind of state of emergency, claiming that the opposition threatened Serbia’s existence. The end goal was the infinite grasp on power in the name of the communist ideology, which they maintained even with the formal fall of communism in 1990.
Keywords: communism; Serbia; the Socialist Party of Serbia; Yugoslavia; elections; sport; culture; economy; monarchy; Serbian Orthodox Church